PROSES PERALIHAN HAK MILIK ATAS TANAH KARENA PEWARISAN DALAM PERKAWINAN CAMPURAN - Irvan, Muhammad; Warman, Kurnia; Arnetti, Sri (Lambung Mangkurat Law Journal, 2019)
Land rights are rights giving authority to the right holder to use the and get the benefit from it.the rights holders is limited by the regulation. Those who may obtain property citizens only and legal entities indonesia based on government regulation. Ownership of the land is hereditary right, strongest and fullest that can be held above the land. But often the ownership of the land has created problems in the communities. One of them is due to the occurrence of a inter-marriage would have an impact on the property over the land for inheritance in marriage a mixture. The law which occurs because the inheritance which causes the transfer of ownership of land did not require nationality, but the provisions of land restrict the ownership of property for land gave it to transfer a land rights over land inherited by foreigners. Then problem identification discussed in research is as follows: (a) how the process of intermarriages according to marriage law? ( b ) how the transition of ownership of the land because the inheritance in intermarriages? ( c ) how strong of property rights of the land because the inheritance in intermarriages? Research methodology used juridical approach is empirical research. Juridical empirical method, the research use approach to the problem, connected with the facts and law happens on the field. The research results show that the process was done based on marriage mingling law from the marriage was done. To ownership rights due to intermediate of the inheritance in marriage a mixture is the same with the transfer ownership rights as the other land inheritance. Along heir who performs marriage intervening who make a break to property by having them land rights.To the heirs who in marriage a mixture still heritage having land rights. If the heirs was for foreigners, they should release at most the due in a year time